An integrated geospatial approach and the factors required to delineate irrigation suitability areas - Nhamo, Luxon; Magidi, James; Mpandeli, Sylvester; Liphadzi, Stanley; Mabhaudhi, Tafadzwanashe (Frontiers in Sustainable Food Systems, 2024)
Most emerging economies rely on agriculture, yet over 90% of the sector remains rainfed, which is characterised by low productivity and is highly susceptible to climate change. The focus now is to increase the irrigated area to boost crop-water productivity under climate change. However, there is varied information on actually irrigated areas and no consensus on the factors that should be used to delineate areas suitable for irrigation. This study defined the factors required to delineate areas suitable for irrigation, including rainfall, landuse, closeness to waterbodies, soil characteristics, and groundwater depth. These physical factors were used to delineate irrigation suitability areas in Monze District, Zambia, applying an integrated geospatial technique and the Analytic Hierarchy Process (AHP), a multi-criteria decision method, in ArcGIS. Socio-economic factors were excluded in this instance as they are only ideal for indicating optimal areas to initiate irrigation projects under a set of given conditions, including crop-specific conditions. Accuracy was assessed by overlaying field points of currently irrigated lands obtained during fieldwork on geospatially delineated irrigation suitability areas created in this study. All the fieldwork points matched the modelled irrigation suitability areas, providing the best possible accuracy of 100%. However, there are vast lands that were also mapped as suitable but are not being irrigated, highlighting the underutilisation of the irrigation potential in the study area. The results are significant for policy decisions on irrigation expansion and development.